Factors associated with visceral-hemolytic loxoscelism in Hospital Nacional Cayetano Heredia between 2000 and 2008 - Webb Camminati, Camille María (2010)
Objectives: To determine clinical factors associated with the occurrence of visceral-hemolytic loxoscelism in patients admitted to Hospital Nacional Cayetano Heredia, and to describe both clinical and epidemiological features of this condition. Material and method: We conducted a case-control study including patients admitted to Hospital Nacional Cayetano Heredia in Lima, Peru, with a diagnosis of visceral-hemolytic loxoscelism (cases) and cutaneous loxoscelism (controls), between years 2000 and 2008. Variable were analyzed using a logistic regression model adjusting for potential confounding factors. Results: Forty-nine cases and 89 controls were included. Age of patients was similar in both groups (33 ± 18 years vs. 31 ± 20 years, p= 0,27). Visceral-hemolytic loxoscelism was associated with spider bites located in the thorax (OR: 7.3; 95% CI: 1.3–41.0) and with systemic manifestations, including fever (OR: 3.2, 95% CI: 1.3–8,1) and a poor general condition (OR: 3.3; 95% CI: 1.3–8.1). Mortality rates were 18% in cases and 0% in controls.   Conclusions: Spider bites located in the thoracic area and the presence of fever and a poor general condition during the first 24 hours of hospitalization are associated with the occurrence of visceral-hemolytic loxoscelism.